Molecular basis of V-ATPase inhibition by bafilomycin A1 - Rong Wang (Nature Portfolio, 2021)
Bafilomycin A1, a member of macrolide antibiotics and an autophagy inhibitor, serves as a specific and potent V-ATPases inhibitor. Here authors report the cryo-EM structure of bafilomycin A1-bound V-ATPase with six bafilomycin A1 molecules bound to the c-ring and reveal the molecular basis for Bafilomycin A1 inhibition of the V-ATPase.